2019
DOI: 10.25134/unifikasi.v6i1.1629
|View full text |Cite
|
Sign up to set email alerts
|

Law Enforcement Model in Community-Based Waste Monitoring and Management as a Realization of Good Environmental Governance Principles in West Sumatera, Indonesia

Abstract: The increasing number of population and industry will have an impact on the number of waste produced, such as plastic waste, paper waste, and packaging products containing toxic materials. This research aims to create a law enforcement model in community-based waste monitoring and management as a realization of the principles of Good Environmental Governance. The research method used was empirical juridical. The results showed that the law enforcement model adapted in community-based waste monitoring and manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Consistency in the handling of data is crucial throughout all stages of the data management process, including postcollection phases. In a recent empirical juridical study conducted by Puspita, Kurnia, and Yevendri (2019), it was discovered that community-led law enforcement monitoring of fellow community members has a significant impact on the implementation of environmental governance programs (Puspita et al, 2019). The present study indicates that monitoring is necessary even in small groups within a community.…”
Section: Solid Waste Management In Indonesiamentioning
confidence: 52%
See 1 more Smart Citation
“…Consistency in the handling of data is crucial throughout all stages of the data management process, including postcollection phases. In a recent empirical juridical study conducted by Puspita, Kurnia, and Yevendri (2019), it was discovered that community-led law enforcement monitoring of fellow community members has a significant impact on the implementation of environmental governance programs (Puspita et al, 2019). The present study indicates that monitoring is necessary even in small groups within a community.…”
Section: Solid Waste Management In Indonesiamentioning
confidence: 52%
“…The success of the Environmental Governance project in West Sumatra is contingent upon several factors, as outlined by Puspita, Kurnia, and Yevendri in their 2019 study. The authors suggest that the level of success achieved by the project will be determined by these factors (Puspita et al, 2019).…”
Section: Solid Waste Management In Indonesiamentioning
confidence: 99%
“…A research by Puspita et.al (2019) has shown how the collaboration between government with the community will resulting a better output. Proper monitoring system and well-managed mechanism of waste need to be existed as part of the policy implementation (Puspita, Kurnia, & Yevendri, 2019). The previous study has shown how solid waste management should be considered and threated as one of governance problem.…”
Section: Introductionmentioning
confidence: 99%